Aktivitas Antimikroba dan Analisis Gen Plantarisin F dari Isolat Lactobacillus Asal Buah-buahan Tropis - TITIN YULINERY; NOVIK NURHIDAYAT (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
Lactobacillus isolated from tropical fruits can be used as probiotic and potential to prevent diseases in the digestive tract due to bacteriocin content. One of the bacteriocin called plantaricin F, is produced by Lactobacillus plantarum. Plantarisin F has antimicrobial activity against Gram positive and Gram negative bacteria. The aim of the research was to test the antibacterial activities of several Lactobacillus species on 5 bacteria isolates, and analyzed the gene expression of plantaricin F. Seven isolates of ten selected isolates could inhibit the growth of Gram positive and Gram negative bacteria. Lactobacillus TB (NK) produced the largest inhibition area of 2.05 cm on E.coli, and twice stronger than chloramphenicol control. As confirmation, the plantaricin F gene was analyzed using RT-PCR. The analysis result showed that the size of plantaricin F gene was 70 bp. The highest relative expression of plantaricin F gene was shown by the Lactobacillus Mar A2 isolate of 10,676 Au, followed by Lactobacillus TB (NK) of 2.9207 Au, and the lowest was Lactobacillus TB (CK) of 0.5141 Au. Lactobacillus TB (NK) can be used as candidate of probiotic and alternative antibiotic in preventing of gastrointestinal disease.